Long‐acting injectable antipsychotics as maintenance therapy for schizophrenia during the COVID‐19 pandemic: A micro‐narrative review - Yoshiyo Oguchi; Nobumi Miyake; Kumiko Ando (Wiley, 2024)
Abstract The coronavirus disease pandemic has presented healthcare systems with unprecedented challenges globally and substantially impacted the management of chronic diseases such as schizophrenia. This narrative review highlights the usefulness of long‐acting injectable antipsychotics (LAIs) as maintenance therapy for patients with schizophrenia during the pandemic. The analysis of relevant literature and psychiatric survey data revealed diverse trends in LAIs prescription and patient adherence with oral antipsychotics. Although some studies have reported a decrease in LAIs prescriptions owing to pandemic‐related disruptions, others have suggested stable patient adherence with oral antipsychotics. Approximately 70% of Japanese psychiatrists reported an increase in schizophrenia relapse rates in a survey, underscoring the critical role of LAIs in maintaining therapeutic stability. The potential benefits of LAIs with extended dosing intervals have been highlighted, including improving oral medication adherence and reducing the frequency of hospital visits. In conclusion, this review emphasizes the continued need for uninterrupted LAIs therapy in conjunction with community and home‐based care despite the disruptions caused by the coronavirus disease pandemic. Further development of LAIs maintenance therapy strategies considering the ongoing pandemic and potential future public health emergencies are required.